Simulation of dwell-to-penetration transition for SiC ceramics subjected to impact of tungsten long rods - Yuan, Jianming (2020)
For a ceramic armour impacted by a long rod projectile, increasing the dwell-to-penetration transition velocity significantly improves its ballistic performance, whereas it can be achieved by prestressing of the ceramic or placing a buffer over the impact surface. In this paper, numerical simulation using the AUTODYN hydrocode is conducted to investigate how dwell-to-penetration transition is affected by the radial prestress and the presence of a buffer. Taking account of the pressure-dependent strength of SiC ceramics, it is found that distribution of hydrostatic pressure and equivalent stress in the ceramics controls damage initiation and dwell to-penetration transition. Ceramic damage initiates from the edge of the projectile and then forms a damaged zone in front of the projectile. Compared to the radial prestress, the buffer more effectively suppresses damage initiation to fulfil interface dwell at a higher transition velocity.